Relations between man and environment in the development of precolonial settlements in the basin of Mexico - Rubén López Recéndez (Investigaciones Geográficas, 2012)
Publicado en: "Interaction of the prehistoric man and his environment". V Symposium of the Commission on Environment Problems, International Geographical Union. Instituto de Geografía, UNAM, Mexico, 1981.